The Application of Technology-Organization-Environment Framework to Analyze SME Readiness in Using Digital Payment Applications - K. Pramudito, Dendy; Achmady, Sayed; Ratna Tungga Dewa, Dominica Maria; Pitri, Tedi; Candrasari Hermanto, Diwahana Mutiara (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to identify the variables that affect SMEs' preparedness to use e-wallets. This study employed a quantitative methodology. This method falls under the experimental research category. Questionnaires were used as the instrument of choice for gathering data. The study's target population consists of SMEs who have made payments using e-wallets. Purposive sampling was the method employed, and 200 samples total were collected. SmartPLS software was used in the data analysis for this study. At this point, the outer model and the inner model were the subjects of two analyses. SMEs are prepared to use e-wallets as a payment method, which is influenced by organizational, technological, and environmental factors, according to the discussion's findings. The most dominant factor influencing SMEs' intentions to use e-wallets is technology. This is followed by organization and the environment. Of the six hypotheses proposed, one was rejected, and the other five were accepted with a significant positive relationship. The hypothesis that is rejected is that environment affects organization. This is because the organizational structure is not yet perfect, causing existing organizational factors not to be determined by competitive pressure or the influence of service providers and partners. The hypothesis that has the greatest influence is that the environment influences technology. The higher the level of perceived pressure from competitors and support from service providers and partners, the higher the organization's intention to use technology.